Принципи роботи ZKP та протокол ідентифікації Шнорра - Наконечний, В. В. (ХНУРЕ, 2024)
Zero-Knowledge Proof is a cryptographic method used in digital authentication to verify information without revealing sensitive data. This allows the parties to confirm the accuracy of the information without revealing the details. This approach is valuable to governments and organizations seeking to protect data privacy while simultaneously verifying information. Zero-knowledge verification is used in a variety of digital contexts, including identity verification, authentication, anti-spam, secure payments, account management, and more.
Keywords: принципи роботи ZKP; протокол ідентифікації Шнорра